Students Mathematical Reflective Thinking Ability in Solving Higher Order Thinking Skills (HOTS) Type Problems as Seen From Cognitive Style - Sari, Yaniswa; Swastika, Annisa; Tanyono, Dillah (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
One of the high-level thinking skills that plays an important role in problem solving is reflective thinking. Reflective thinking helps students think about what they do and why they do it. In fact, this ability is still in the low category. Each student has different characteristics. This is related to the way a person absorbs and processes the information they receive, resulting in different ways of thinking in solving problems. The purpose of this study was to describe the mathematical reflective thinking skills of students with dependent cognitive styles and independent cognitive styles when solving HOTS-type problems. This study involved teachers and students at SMK Muhammadiyah 1 Surakarta. The data collection method in this study was the test and interview method and will be analyzed using descriptive analysis. The results showed that students with independent cognitive styles were able to meet all indicators of reflective thinking, such as reaction, evaluation, and reflection. Students with dependent cognitive styles were unable to meet the three indicators of reflective thinking. Students with domain dependent cognitive styles were only able to meet the reaction indicator, but the evaluation and reflection indicators had not been met. It can be said that students with domain independent cognitive styles solve problems more thoroughly than students with domain dependent cognitive styles.